2014
DOI: 10.3324/haematol.2013.091405
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia nurse-like cells express hepatocyte growth factor receptor (c-MET) and indoleamine 2,3-dioxygenase and display features of immunosuppressive type 2 skewed macrophages

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nderived from co-culture of monocytes and autologous leukemic cells are characterized by a gene expression profile typical of cells with dysregulated immunocompetence which could be relevant in the context of the acquired immunodeficiency commonly found in CLL patients. 12Whether NLC represent CLL-specific tumor-associated macrophages, as recently suggested, 13 is still debated. We have recently reported that hepatocyte growth factor (HGF), together with CXCL12, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…25,37,38 Few studies were conducted on B-cell lymphomas or CLL, which focused exclusively on the M-MDSC subtype. [27][28][29]39 Because the majority of blood biomarkers in DLBCL are linked to tumor microenvironment and in particular to myeloid cell biology, 6,7,14-17 further characterization of the MDSC compartment is highly relevant in this disease. Our aim, in this study, was to characterize the various MDSC subsets in peripheral blood from DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…25,37,38 Few studies were conducted on B-cell lymphomas or CLL, which focused exclusively on the M-MDSC subtype. [27][28][29]39 Because the majority of blood biomarkers in DLBCL are linked to tumor microenvironment and in particular to myeloid cell biology, 6,7,14-17 further characterization of the MDSC compartment is highly relevant in this disease. Our aim, in this study, was to characterize the various MDSC subsets in peripheral blood from DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…33,44 It is well known that monocytes isolated from CLL patients have immunosuppressive properties characterized by a strong reduction in T-cell proliferation, and this anti-proliferative effect is caused, in part, by TGFβ, IDO1 and IL10. 5,7,21 We observed that lenalidomide is able to improve the ability of NLCs to stimulate T-cell proliferation. In line with these findings, a switch of NLCs properties to a pro-inflammatory profile was supported by gene expression profiling analysis.…”
Section: Discussionmentioning
confidence: 79%
“…45 The role of IDO1 in the immune response is still controversial, implying a possible involvement in M1 polarization or alternatively in immune tolerance. 7,46,47 Lenalidomide up-regulated IDO1 expression in NLCs. One possible explanation may account for the counter regulatory role of IDO1 to restrain excessive or inappropriate immune activation during an inflammatory response mediated by lenalidomide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations